Outcome of Endodontic Treatments Made by Postgraduate Students in the Dental Clinic of Bretonneau Hospital. (20th March 2014) - Touboul, Virginie; Germa, Alice; Lasfargues, Jean-Jacques; Bonte, Eric
Abstract : Objective . The objective of this retrospective study is double: (1) to assess the 1–4 years of outcome of endodontic treatment performed by postgraduate students in endodontics in the Dental Clinic of Bretonneau Hospital and (2) to examine outcome predictors. Method . 363 teeth in 296 patients were treated between 2007 and 2011. 183 patients (224 teeth) were lost during the followup. 113 patients were included in the study (recall: 38%), corresponding to 139 teeth of which 8 were extracted. 131 remaining teeth (36%) were examined clinically and radiographically. Apical periodontitis (AP) was absent (PAI = 1) or present (PAI ≥ 2). Outcome was classified as "healed, " "healing, " or "diseased". Results . The success rate was 92%. No failure was observed among the 23 initial endodontic treatments. Among the 108 retreated teeth, 80% were "healed" and 11% were "healing." An association was found between success rate and preoperative signs or symptoms (absent 95% versus present 83%), preoperative root filling density (inadequate 93% versus adequate 57%), but not between preoperative AP status and success. Conclusion . Outcomes in this retrospective study were similar to those previously reported. However, a larger sample size is needed to assess outcome predictors more precisely.